The Effectiveness of Applying Fraction Card Block Media to the Understanding of Fraction Arithmetic Operation Concepts in Grade IV Elementary School Students - Sarwati Sarwati; Maisura Maisura; Ety Mukhlesi Yeni (FKIP - Universitas Riau, 2026)
This study aimed to determine the effectiveness of Fraction Card Block Media in improving fourth-grade elementary students’ understanding of fraction operations. The research employed a quantitative approach using a quasi-experimental method with a non-equivalent comparison-group design involving an experimental class and a control class. Data were analyzed using normality tests, homogeneity tests, and paired-sample t-tests. The results of the Kolmogorov–Smirnov and Shapiro–Wilk tests showed significance values greater than 0.05, indicating that the data were normally distributed. The homogeneity test also indicated homogeneous data with a significance value of 0.390 (>0.05). Furthermore, the paired-sample t-test results showed that the experimental class experienced a significant improvement in understanding fraction operations, with a significance value of 0.000 (<0.05), while the control class showed no significant improvement, with a significance value of 0.078 (>0.05). These findings indicate that Fraction Card Block Media is effective in enhancing students’ conceptual understanding of fraction operations. The use of concrete and visual learning media can help students better understand abstract mathematical concepts and support more effective learning processes.